Recent advances in the synthesis of trifluoromethyl-containing heterocyclic compounds via trifluoromethyl building blocks - Liu, Yaopeng; Tian, Qingyu; Ge, Jin; Wu, Xi; Li, Zhenghao; Cheng, Guolin (Organic & biomolecular chemistry, 2024)
Trifluoromethylated heterocyclic compounds have played an increasingly significant role in pharmaceuticals, agrochemicals, and materials. This is because the introduction of trifluoromethyl could enhance the lipophilicity, metabolic stability, and pharmacokinetic properties of heterocyclic drug molecules. Therefore, the synthesis of trifluoromethylated heterocyclics has become a major subject of research. The construction of trifluoromethylated heterocyclics via the annulation of trifluoromethyl building blocks with suitable partners has been proved to be a powerful strategy. In this review, we systematically summarize and discuss recent advances in the preparation of trifluoromethyl-containing heterocyclics via trifluoromethyl building block strategies over the period from 2019 to the present.